Road Traffic Injury deaths and Correlates in Babylon Province: A Cross- Sectional Study - Sahar Adham Ali1 , Hasan Alwan Baiee2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Road traffic accidents were a major health problem especially in low and middle incomecountries including Iraq, head injuries were found to be the most common fatal injuries during trafficaccidents that causing deaths.Objectives: to identify the relationship of road traffic injury deaths with different associated factors and tomeasure the extent of this problem.Methodology: this was a cross-sectional study included a retrospective analysis of the forensic medicinedata presented in the records of forensic medicine department for three years (2017-2019) the period neededto conduct this study started from 1st of February to the end of November,2019 . After the approval of thestudy protocol by the Babylon nursing college health ethical committee , a semi structured questionnaire wasused to collect data according to the descriptive epidemiologic model (person , place, time).Results: The road traffic accidents death rate in Babylon province was unacceptably high, the mean deathsper month due to Road Traffic Injuries was 43,8 and the mean deaths per week was11victims and the crudedeath rate =27/100000 population; Males in their productive age group were outnumbered victims to thispreventable high priority health problem. Urgent interventional plan of action including provision highquality nursing tertiary care should be started to address this growing problem using the available resourcesto promote the critical care skills among health care providers and to reduce medical errors.